The effect of nutritional status on arch width and length of primary teeth among five years old kindergarten children - Zaid SH Ahmed; Ban S Diab (College of Dentistry/ University of Baghdad, 2015)
Background: In human life, malnutrition may adversely affect various aspects of growth at different stages of life. Teeth are particularly sensitive to malnutrition. Malnutrition may affect odontometeric measurement involving arch width and length of primary dentition. The aim of this study is to estimate the effect of nutrition on arch width and length dimension measurements among children aged 5 years old. Material and methods: This study was conducted among malnourished group in comparison to well-nourished group matching with age and gender. The present study included 158 children aged 5 years (78 malnourished and 80 well-nourished). The assessment of nutritional status was done by using three nutritional indicators, namely Height-for-age, Weight-for-age and Weight-for-height. Odontometeric measurements including two different orientations. For both upper and lower study models, photographs were taken using special photographic apparatus for each child, and the data were then analyzed using special computer software. For primary dentitions, two linear measurements (inter-canine distance and inter-molar distance) were utilized, representing arch measurements. Results: As for primary dentitions, all means value of maxillary and mandible arch width and length were lower among malnourished group than well-nourished group with statistically highly significant except for both inter-canine distance of maxillary and mandibular, maxillary anterior arch length and mandibular molar vertical length. Conclusion: Malnutrition effect on minimize the odontometric measurements (dental arch width, dental arch length) among children aged 5 years.